Seasonal population dynamics of Octopus vulgaris in the eastern Mediterranean - Katsanevakis, S.; Verriopoulos, G. (ICES Journal of Marine ScienceICES Journal of Marine Science, 2006)
The population density of Octopus vulgaris was measured by visual census with scuba diving in coastal areas in Greece (eastern Mediterranean). A time-variant, stage-classified, matrix population model was developed to interpret the seasonal variation of octopus stage densities and to estimate several life cycle parameters. An annual and a semi-annual periodic cycle were found in the stage densities. A main peak of benthic settlement was observed during summer and a secondary, irregular one during late autumn. Two spawning peaks were estimated, a main one during late winter-spring and a secondary one during late summer-early autumn. More than 50% of the just-settled individuals will eventually die after 3 months. Mortality rate declines, as individuals grow larger, reaches a minimum approximately 6 months after settlement, and then grows again probably because of terminal spawning. The life expectancy of recently settled individuals (<50 g) during their summer peak is approximately 5 months. The lifespan of the common octopus is estimated to be between 12 and 15 months. The octopuses' mean specific growth rates (±s.d.) in their natural environment were 1.61 ± 0.30 d -1 for 50-200 g individuals and 1.19 ± 0.31 d-1 for 200-500 g individuals. © 2005 International Council for the Exploration of the Sea. Published by Elsevier Ltd. All rights reserved.
Keywords: abundance; growth; Matrix population model; Mollusca Cephalopoda; mortality; octopus; Population dynamics; Seasonal variation; Settlement; spawning